2018
DOI: 10.20884/1.jm.2018.13.1.410
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoid Compounds from The Stembark of Aglaia minahassae (Meliaceae)

Abstract: Two sesquiterpenoid compounds, 4(15)-eudesmen-1,6-diol (1) and spathulenol (2) have been isolated from the stembark of Aglaia minahassae belong to Meliaceae family. The chemical structures of 1 and 2 were identified on the basis of spectroscopic evidence including UV, IR, NMR 1D, NMR 2D as well as mass spectra and by comparison with those previously reported spectra data. This compounds were isolated from this plant for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…3). The detailed examination of the NMR spectral data and comparison with those reported for 4α,10α-dihydroxyaromadendrane [14,16] showed that the structures of these two compounds are very similar. Therefore, the structure of compound 3 was determined to be 4α,10α-dihydroxyaromadendrane.…”
Section: In Vitro Cytotoxic Activity Assaymentioning
confidence: 77%
See 1 more Smart Citation
“…3). The detailed examination of the NMR spectral data and comparison with those reported for 4α,10α-dihydroxyaromadendrane [14,16] showed that the structures of these two compounds are very similar. Therefore, the structure of compound 3 was determined to be 4α,10α-dihydroxyaromadendrane.…”
Section: In Vitro Cytotoxic Activity Assaymentioning
confidence: 77%
“…A. harmsiana is one of Aglaia plants that has been phytochemically investigated before and it has been proven to contain cycloartane triterpenoids [11][12] and rocaglamide derivative with insecticidal activity [13]. In total, less than ten aromadendrane-type sesquiterpenoids were investigated separately from the Aglaia species [14][15], and this type of compound did not attract considerable attention [16].…”
Section: ■ Introductionmentioning
confidence: 99%
“…These functionalities accounted for one out of the total four hydrogen deficiency index. Three remaining hydrogen deficiency index was corresponded to the tricyclic sesquiterpenoid structure and one cyclic comes from an epoxide group (Kurniasih et al, 2018;Roux et al, 1998;Liu et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Aglaia species which have been shown to contain sesquiterpenoid compounds are A. minahassae (Kurniasih et al, 2018), A. foveolata (Roux et al, 1998), A. odorata (Liu and Xu, 2016), A. silvestris (Poitinger et al, 2008), A. grandis (Inada et al, 2000), A. perviridis (Pan et al, 2013) and A. leucophylla (Benosman, Richomme, Sevenet, Hadi & Bruneton, 1994) with six sesquiterpenoid groups, namely sesquiterpenoid eudesmane, guaiane, aromadendrane, cadinene, isodaucane, and caryophyllene. Caryophyllene-type sesquiterpenoids, particularly caryophyllene oxide, has showed cytotoxic activity against various cancer cell lines, such as HepG2, AGS, HeLa, SNU-1, and SNU-16 (Jun et al, 2011) Although sesquiterpenoids of other Aglaia species have been investigated previously, the sesquiterpenoid compounds of the stem bark of A.…”
Section: Introductionmentioning
confidence: 99%
“…Meliaceae is well known as a source of diverse natural compounds with interesting biological activity. Some compounds including sesquiterpenoids [2][3][4][5][6][7], triterpenoids [8][9][10][11][12][13][14][15][16][17][18], diterpenoids [19][20][21], steroids [22][23][24][25], limonoids [26][27], alkaloids [28][29], lignan [30][31][32], flavaglines [33][34][35], and flavonoids [36][37] have been successively extracted from this family. Those isolated compounds showed interesting biological activities including cytotoxic [38][39][40][41], insecticidal [42][43], antimycobacterial [6], antifungal [44][45], antiinflammatory [9,[46]…”
Section: ■ Introductionmentioning
confidence: 99%